(untitled) (Comprehensive Journal of Science, 2025)
Background and Aim: Helicobacter pylori infection represents a major global health challenge, with epidemiological patterns showing considerable geographic variation. This investigation sought to evaluate the current status of H. pylori infection within a patient population in Al-Bayda, Libya, focusing on infection frequency and its correlation with key demographic variables. Methods: This observational analysis was carried out between 2024 and 2025. The study cohort comprised 748 individuals. Detection of H. pylori was performed using enzyme-linked immunosorbent assay (ELISA) techniques on two sample types: serum for quantifying specific IgG antibodies and stool for identifying bacterial antigens. Results: Laboratory analysis identified a positive infection rate of 39.3%. The data revealed a higher frequency of positive results among female participants (64.6%) compared to male